The characterization through film images in the work of Manuel Rivas - Castro Otero, Salvador (Tropelías: Review of Literary Theory and Comparative Literature, 2018)
This paper defends the influence of cinema on contemporary literary narrators, especially in Manuel Rivas. It tries to show how this creator uses elements of the cinema (especially actors and characters) to characterize people or creatures of his own fiction. At the same time, the interpretation of the films or the heroes also constitute a characterizing element.
Keywords: Manuel Rivas; Comparative literature; cinema and literature; Journalism; Characterization